Comparison of fatigue levels, muscle strength, balance, and exercise performance of young adults with a history of mild covid-19 and healthy adults - KILIÇ, TALHA; YILDIZ ÖZER, AYSEL (My University, 2023)
Aim: The coronavirus disease-2019 (COVID-19) infection directly impacts fatigue and exercise performance. More studies have focused on these problems and were conducted with hospitalized patients and/or adult and geriatric populations. The aim of this study was to explore the effects of mild COVID-19 on fatigue, muscle strength, balance, and exercise performance, specifically in young adults. Methods: This research was designed as a case-control study, and tests were conducted between January 2022 and June 2022. The study included 60 participants aged 18-28, consisting of individuals who had a mild COVID-19 diagnosis within the past year (study group, n=30) and tested negative during the study, as well as a control group of individuals who had no COVID-19 diagnosis or symptoms within the past year (control group, n=30). The participants’ fatigue levels (Chalder Fatigue Scale), lower (Biodex Isokinetic-Dynamometer) and upper (Jamar-Handgrip Dynamometer) extremity muscle strength, balance (Y-Balance Test), and exercise performance (Queen’s College Step Test) were evaluated using various standardized tests. Results: Measurements showed that individuals with COVID-19 had an increase in fatigue scores (p=0.02). It was determined that fatigue was particularly prominent in women. Due to this difference that arose according to gender, it was observed that fatigue scores in those who had experienced COVID-19 were negatively correlated with muscle strength measurements. Conclusion: This study showed that symptoms of fatigue persisted in younger individuals, especially women, even after the COVID-19 infection. We think the next research should focus on COVID-19 symptoms, surveillance, and therapy in different age groups.
Keywords: Sağlık Bilimleri; Fizyoterapi ve Rehabilitasyon; Health Sciences; Physical therapy and rehabilitation; Klinik Tıp (MED); Klinik Tıp; REHABİLİTASYON; Clinical Medicine (MED); CLINICAL MEDICINE; REHABILITATION; Fizik Tedavi, Spor Terapisi ve Rehabilitasyon; Kayropraktik; Rehabilitasyon; Physical Therapy, Sports Therapy and Rehabilitation; Chiropractics; Rehabilitation